Integration of alternative energy sources into digital micro‐grids. Issue 1 (12th September 2017) - Rojas‐Cessa, Roberto; Grebel, Haim; Jiang, Zhengqi; Fukuda, Camila; Pita, Henrique; Chowdhury, Tazima S.; Dong, Ziqian; Wan, Yu
Abstract : We overview different alternative energy resources and comment on their benefits and challenges. We highlight some features of alternative and sustainable energy resources and discuss some challenges for their integration into the power grid. In view of global trend toward blending alternatives and conventional energy resources in electrical power grids, a more robust energy distribution approach is necessary. Here, we present an alternative to the power grid with great potential for integrating alternative energy sources and defining microgrids—the Controlled‐Delivery Grid (CDG). We comment how this new digital approach enhances the distribution of energy may help to resolve those challenges. We also examine the role of energy storage elements (batteries, super‐capacitors), and sustainable energy resources in this new approach to the power grid. We provide some numerical analysis on the performance of energy distribution of the CDG and some experimental results that highlight some of its features. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 155–164, 2018